1998
DOI: 10.1007/bf03340004
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of eating disordered symptoms in the Korean general population using a Korean version of the Eating Attitudes Test

Abstract: These results suggest that changes in various sociocultural aspects have increased the risk of developing eating disorders in Korea, and support the sociocultural hypothesis of eating disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 39 publications
1
18
0
3
Order By: Relevance
“…[1][2][3] An epidemiological study of eating pathology in South Korea identified rates similar to those found in the West. 4 In a cross-cultural study, Lippincott and Hwang 5 found similar EAT-26 scores in female white students in the United States and female Korean students in Korea. These studies attributed disordered eating in Korean women to Westernization.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…[1][2][3] An epidemiological study of eating pathology in South Korea identified rates similar to those found in the West. 4 In a cross-cultural study, Lippincott and Hwang 5 found similar EAT-26 scores in female white students in the United States and female Korean students in Korea. These studies attributed disordered eating in Korean women to Westernization.…”
Section: Introductionmentioning
confidence: 89%
“…We obtained data on 937 NK women (mean (SD) age ¼ 22.8 [2.6] years) from a previous study that measured eating attitudes and behaviors in the Korean general population. 4 Participants from the study carried out by Lee and colleagues were selected to match the age of participants recruited in the United States; thus, the groups did not differ significantly in age (p ¼ .52).…”
Section: Samplementioning
confidence: 99%
“…Scores on the Korean EAT-26 were positively related to body dissatisfaction (Y. H. Lee et al, 1998) and body shame (S. Kim et al, 2010) among South Korean women. Cronbach's alphas for EAT-26 items have ranged from .79 to .94 across samples of U.S. women (Kashubeck-West et al, 2001;Mazzeo, 1999), and the value was found to be .80 in a sample of South Korean women (Y. H. Lee et al, 1998); Cronbach's alpha for the current study was .90.…”
Section: Instrumentsmentioning
confidence: 96%
“…They also reported that Korean college women scored higher than a comparison sample of Korean-American college women on the dieting and bulimia subscales of the Eating Attitudes Scale (EAT, Garner, Olmstead, Bohr, & Garfinkel, 1982). Similarly, Lee et al (1998) reported a relatively high level (8.5%) of extreme scores on the EAT in a representative sample of Korean adults. In addition, the incidence of cosmetic surgery appears to be high in Korea (White, 2005).…”
mentioning
confidence: 86%